SEAWEED CULTIVATION KAPPAPHYCUS ALVAREZII SUBOH DOTY IN SITUBONDO EAST JAVA - Mohammad mahmudi; kusriani kusriani; putut wijanrko (Journal of Innovation and Applied Technology, 2016)
This study aims to determine the rate of daily growth and productivity of seaweed K. alvarezii and economic value in the Gelung Coastal to support the production of seaweed K. alvarezii. This research was conducted in August-October 2015 in the Gelung Coastal Desa Gelung Kecamatan Panarukan Kabupaten Sitobondo, East Java. Seaweed seeds of K. alvarezii (0:47 ± 2.99) kg grown using a rope tied to a rope stretch of No. 4 and mounted on a bamboo raft (6 x 7) m2. Seaweed weighing done at the beginning and end of the study. Water quality measured in the form; Temperature (oC), Salinity (ppt), Brightness (cm), pH, Nitrite, Nitrate, Ammonium and posphate. Data growth and productivity of seaweed K. alvarezii were analyzed descriptively. Analysis of the economic aspects of cultivation of macroalgae covering the analysis of BEP (Break Event Point), ROI (Return on Investment) and B / C ratio (Benefit Cost Ratio) to determine how the feasibility of seaweed cultivation K. alvarezii sustainable.This results showed that the average weight of seaweed is (10:55 ± 1.67) kg each rope stretch of the shelf that are kept for 35 days. Weight gain seaweed K. alvarezii reached 4 times the initial weight (2.99 ± 0:47) kg with an average daily weight gain reached 23% and specific growth rate (SGR) is 3.92%. Daily growth rate seaweed K alvarezii is almost identical to that maintained in the waters of India (Kotiya, et al., 2011), but lower than the daily growth specifically in the waters of Yucatan, Mexico (monoz et al. 2004) and the results of tissue culture (Lym Yong et al. 2014), but higher than with a specific daily growth Sangihe Islands waters Talengan Minahasa which only reaches 3:37% (Tiwa, et al. 2013). Similarly, the productivity of seaweed farming in the coastal Gelung shelf models more productive with average results obtained reached 4.76 kg / m2 or 47.6 tons / ha. Much higher result compared with the East India Water Tharuvaikulam until reach 2:59 kg / m2 (Athithan, 2014) and in the waters of Southeast Sulawwesi Konawe reaching only 1:34 kg / m2 (Faisal, et al. 2013). This is due to the nutrients that need seaweads K. alvarezii Aquatic Gelung sufficient. Based on the economic analysis of seaweed cultivation K. alvarezii BEP values obtained with the production 1.880.91 kg dry. The value of ROI obtained was 0.77 or 77%. This means that for every capital of Rp. 100.00, - obtained a profit of Rp. 77.00. while the value of B / C ratio obtained is of 1.77 which means that with a capital of Rp. 13,165.000 be obtained from the sale of 1.77 times the amount of capital. Based on the analysis of K. alvarezii seaweed cultivation and economic analysis that seaweed K. alvarezii farming in the coastal Gelung Situbondo worth the effort